Advancements in microwave dielectric ceramics with K20 for 5G/6G communication systems: a review - He, Guo Qiang; Miao, Jin Chao; Wu, Fang Fang; Wang, Wei; Bao, Jian; Jiang, Jia Pei; Liu, Da Wei; Darwish, Moustafa Adel; Zhou, Tao; Xu, Di Ming; Xia, Song; Tan, Kar Ban; et al. (Royal Society of Chemistry, 2025)
The rapid advancement of 5G and 6G communication systems has driven the need for high-performance microwave dielectric ceramics, which are essential for enabling ultra-high-frequency signal transmission, device miniaturization, and thermal stability. These materials must meet stringent requirements, including ultralow dielectric loss (tan δ < 10−4), near-zero temperature coefficient of resonant frequency (τf ≈ 0 ppm °C−1), and tunable permittivity (ϵr ≈ 20), to support the growing demands of emerging technologies such as the Internet of Things (IoT), autonomous vehicles, and augmented reality (AR). This review provides a comprehensive analysis of recent progress in microwave dielectric ceramics with ϵr ≈ 20, focusing on four key material systems: MgTiO3-CaTiO3, (Ca,La)(Al,Ti)O4, LnNbO4, and Li2TiO3. We explore innovative material design strategies, including ion doping, composite modification, and advanced sintering techniques, to optimize dielectric properties such as quality factor (Q × f), temperature stability, and permittivity. Furthermore, we highlight breakthroughs in device applications, including dielectric resonator antennas (DRAs) and millimeter-wave antenna arrays, demonstrating the practical potential of these materials in 5G/6G communication systems. Future perspectives emphasize the development of high-entropy ceramics, machine-learning-guided material discovery, multifunctional and adaptive materials, and sustainable manufacturing practices. This review aims to provide a thorough understanding of the state-of-the-art in microwave dielectric ceramics, offering valuable insights for researchers and engineers working on next-generation high-frequency communication technologies.